Prevalence of and association between atopic dermatitis and food sensitivity, food allergy and challenge‐proven food allergy: A systematic review and meta‐analysis. (8th February 2023) - Christensen, M. O.; Barakji, Y. A.; Loft, N.; Khatib, C. M.; Egeberg, A.; Thomsen, S. F.; Silverberg, J. I.; Flohr, C.; Maul, J. T.; Schmid‐Grendelmeier, P.; Halling, A. S.; Vittrup, I.; et al.
Abstract: Atopic dermatitis (AD) and food allergy (FA) share similar type 2 inflammation and commonly co‐occur, but the precise proportion of AD patients with FA and vice versa, as well as the effect of AD disease severity on the strength of this association remains uncertain. The aim of this comprehensive systematic review and meta‐analysis was to determine the prevalence and bidirectional associations of AD with food sensitivity (FS), FA and challenge‐proven food allergy (CPFA). We searched PubMed and EMBASE and three independent reviewers performed title/abstract and full‐text review and data extraction. Overall, 557 articles ( n = 225, 568 individuals with AD, n = 1, 128, 322 reference individuals; n = 1, 357, 793 individuals with FS, FA or CPFA, n = 1, 244, 596 reference individuals) were included in quantitative analyses. The overall pooled prevalence of FS, FA and CPFA in individuals with AD were 48.4% (95% confidence interval: 43.7–53.2), 32.7% (28.8–36.6) and 40.7% (34.1–47.5) respectively. AD prevalence among individuals with FS, FA and CPFA were 51.2% (46.3–56.2), 45.3% (41.4–49.3) and 54.9% (47.0–62.8) respectively. Children with AD had higher pooled FS (49.8% (44.4–55.1)) and FA (31.4% (26.9–36.1)) prevalences than adults with AD (28.6% (13.4–46.8) and 24.1% (12.1–38.7) respectively). Prevalences of FS and FA numerically increased with AD severity. FS, FA and CPFA are common comorbidities of AD and are closely related. Physicians should be attentive to this relationship to optimize management and treatment strategies in patients.